Integral dx/x+√x^2+x+1.?

1 Answer
Jun 23, 2018

intdx/(x+sqrt(x^2+x+1))=(sqrt(x^2+x+1)-x)+ln|x+1|-1/2ln|2x+1+2sqrt(x^2+x+1)|+ln|((2-sqrt3)(sqrt3+2sqrt(x^2+x+1))+(2x+1))/((2-sqrt3)(sqrt3+2sqrt(x^2+x+1))-(2x+1))|

Explanation:

Let

I=intdx/(x+sqrt(x^2+x+1))

Rationalize:

I=intdx/(x+sqrt(x^2+x+1))*(x-sqrt(x^2+x+1))/(x-sqrt(x^2+x+1))

Simplify:

I=int(sqrt(x^2+x+1)-x)/(x+1)dx

Rearrange:

I=intsqrt(x^2+x+1)/(x+1)dx-int(1-1/(x+1))dx

Complete the square in the square root:

I=1/2intsqrt((2x+1)^2+3)/(x+1)dx-(x-ln|x+1|)

Apply the substitution 2x+1=sqrt3tantheta:

I=1/2int(sqrt3sectheta)/(sqrt3/2tantheta+1/2)(sqrt3/2sec^2thetad theta)-x+ln|x+1|

Simplify:

I=3/2intsec^2theta/(sqrt3tantheta+1)secthetad theta-x+ln|x+1|

Since sec^2theta=tan^2theta+1:

I=1/2int(sqrt3tantheta-1+4/(sqrt3tantheta+1))secthetad theta-x+ln|x+1|

Rearrange:

I=1/2int(sqrt3secthetatantheta-sectheta)d theta+2int1/(sqrt3sintheta+costheta)d theta-x+ln|x+1|

Apply the appropriate double-angle trigonometric identities:

I=1/2(sqrt3sectheta-ln|sqrt3sectheta+sqrt3tantheta|)+2intsec^2(theta/2)/(2sqrt3tan(theta/2)+1-tan^2(theta/2))d theta-x+ln|x+1|

Complete the square in the denominator:

I=1/2(sqrt3sectheta)-1/2ln|sqrt3sectheta+sqrt3tantheta|+2intsec^2(theta/2)/(4-(tan(theta/2)-sqrt3)^2)d theta-x+ln|x+1|

Apply partial fraction decomposition:

I=1/2(sqrt3sectheta)-1/2ln|sqrt3sectheta+sqrt3tantheta|+1/2int(1/(2+tan(theta/2)-sqrt3)+1/(2-tan(theta/2)-sqrt3))sec^2(theta/2)d theta-x+ln|x+1|

Integrate directly:

I=1/2(sqrt3sectheta)-1/2ln|sqrt3sectheta+sqrt3tantheta|+(ln|2+tan(theta/2)-sqrt3|-ln|2-tan(theta/2)-sqrt3|)-x+ln|x+1|

Apply the trigonometric identity tan(theta/2)=tantheta/(1+sectheta):

I=1/2(sqrt3sectheta)-1/2ln|sqrt3sectheta+sqrt3tantheta|+ln|((2-sqrt3)(sqrt3+sqrt3sectheta)+sqrt3tantheta)/((2-sqrt3)(sqrt3+sqrt3sectheta)-sqrt3tantheta)|-x+ln|x+1|

Reverse the substitution:

I=1/2sqrt((2x+1)^2+3)-1/2ln|2x+1+sqrt((2x+1)^2+3)|+ln|((2-sqrt3)(sqrt3+sqrt((2x+1)^2+3))+(2x+1))/((2-sqrt3)(sqrt3+sqrt((2x+1)^2+3))-(2x+1))|-x+ln|x+1|

Collect terms:

I=(sqrt(x^2+x+1)-x)+ln|x+1|-1/2ln|2x+1+2sqrt(x^2+x+1)|+ln|((2-sqrt3)(sqrt3+2sqrt(x^2+x+1))+(2x+1))/((2-sqrt3)(sqrt3+2sqrt(x^2+x+1))-(2x+1))|